2020
DOI: 10.1101/2020.08.19.257162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centrosome amplification mediates small extracellular vesicles secretion via lysosome disruption

Abstract: Bidirectional communication between cells and their surrounding environment is critical in both normal and pathological settings. Extracellular vesicles (EVs), which facilitate the horizontal transfer of molecules between cells, are recognized as an important constituent of cell-cell communication. In cancer, alterations in EVs secretion contribute to the growth and metastasis of tumor cells. However, the mechanisms underlying these changes remain largely unknown. Here, we show that centrosome amplification is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Exposure to the calcium ionophore ionomycin can also increase exosome secretion via the same mechanism [100]. It has been reported that lysosome dysfunction prevents efficient lysosome and multivesicular body fusion, which will promote EV secretion [101]. Through incubating cells with 20 mM ammonium chloride for up to 7 days, or with 200 nM bafilomycin A1 for up to 72 h, Alvarez-Erviti et al achieved lysosomal inhibition of human neuroblastoma cells SH-SY5Y, leading to an increase in exosome release [102].…”
Section: Increasing Ev Productionmentioning
confidence: 99%
“…Exposure to the calcium ionophore ionomycin can also increase exosome secretion via the same mechanism [100]. It has been reported that lysosome dysfunction prevents efficient lysosome and multivesicular body fusion, which will promote EV secretion [101]. Through incubating cells with 20 mM ammonium chloride for up to 7 days, or with 200 nM bafilomycin A1 for up to 72 h, Alvarez-Erviti et al achieved lysosomal inhibition of human neuroblastoma cells SH-SY5Y, leading to an increase in exosome release [102].…”
Section: Increasing Ev Productionmentioning
confidence: 99%
“…Numerous cancer types usually show defects in the structure and number of centrosomes. Research reports have shown that the presence of excessive centrosomes can increase the secretion of exosomes, and that lysosomal dysfunction causes cells with extra centrosomes to secrete more exosomes in PDAC (108,109).…”
Section: Exosomes Act As Cancer Biomarkersmentioning
confidence: 99%
“…Secretion of ligands such as FGF2, PDGF, TGF-β, CSF-1 and CTGF by activated PSCs has been shown to promote cancer cell proliferation and invasion [ 18 , 19 , 20 , 21 ]. Extra-cellular vesicles may act as carriers for many of the growth factors [ 22 ]. Reversal of PSC activation, by All-trans retinoic acid (ATRA) or tamoxifen, can decrease actomyosin contractility and, therefore, prevent ECM remodeling and invasion, as well as reducing cancer cell proliferation [ 15 , 23 , 24 ].…”
Section: A Role For Pscs In Pdac Invasionmentioning
confidence: 99%